Gambaran perilaku masyarakat dalam pemberantasan sarang nyamuk demam berdarah dengue (PSN DBD) dan kemampuan mengamati jentik di wilayah kerja Puskesmas Banjarangkan II - Rubagan Chelvam; I Gede Ngurah Indraguna Pinatih (Intisari Sains Medis, 2017)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus infection which transmitted through Aedes aegypti mosquito bite and still a public health problem in tropical or subtropical areas worldwide.Â  One of the efforts which are considered appropriate in the prevention and eradication of DHF through cut the chain of transmission and controlling the vectors by eradication of mosquito nest caused Dengue Hemorrhagic Fever (PSN DBD). This study used cross sectional design in Puskesmas Banjarangkan II to describe the peopleâ€™s behavior in eradicating mosquito nest caused DHF. Minimum sample size is 35 people which cover 6 villages and 26 hamlets (banjar)/environments in it. The results showed respondents who have poor PSN DBD behavior aound 57.1% and good around 42.9%. Based on the ability to monitor larvaes, respondents who have poor capabilities to observing it around 62.9% whereas who having good capabilitiesapproximately 31.1%. Accordingly, it can be concluded most of the people who included within the scope of Puskesmas banjarangkan II have poor PSN DBD capabilities as well as observing larvae so that it is necessary to do some attempts to overcome it.Â